2021
DOI: 10.1016/j.cub.2021.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a seismic survey on movement of free-ranging Atlantic cod

Abstract: Effects of a seismic survey on movement of freeranging Atlantic codHighlights d A full-scale seismic survey affected free-ranging cod behavior in multiple ways d Cod left the area earlier than expected, 2 days to 2 weeks after the survey d Cod became less active during the seismic sound exposure, and likely foraged less d Repeated passage of the survey vessel disrupted the diurnal activity cycle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…As a final remark, we like to emphasise that the validity of ABMs heavily depends on the quality of empirical data and the availability of quantitative data for parameters that turn out to be critical for population consequences in sensitivity analyses (Soudijn et al 2020, Gallagher et al 2020). The fact that it is for example often very difficult to get a species‐specific dose‐response threshold or curve for particular behavioural or physiological responses is a major concern (Harris et al 2018, van der Knaap et al 2021). However, it is a concern for which we do see perspective in ABM.…”
Section: Discussionmentioning
confidence: 99%
“…As a final remark, we like to emphasise that the validity of ABMs heavily depends on the quality of empirical data and the availability of quantitative data for parameters that turn out to be critical for population consequences in sensitivity analyses (Soudijn et al 2020, Gallagher et al 2020). The fact that it is for example often very difficult to get a species‐specific dose‐response threshold or curve for particular behavioural or physiological responses is a major concern (Harris et al 2018, van der Knaap et al 2021). However, it is a concern for which we do see perspective in ABM.…”
Section: Discussionmentioning
confidence: 99%
“…Bruce et al (2018) showed that anthropogenic noise cause changes in diurnal local activity patterns and general swimming speed shifts of marine fishes and therefore may negatively affect the catchability of marine fish catchability and the. van der Knaap et al (2021) demonstrated in a field study that Atlantic cod ( Gadus morhua) left noisy areas more quickly and decrease their swimming activity compared to the ambient sound treatment. They also have shown that seismic surveys can disrupt diurnal activity cycles which may have long term negative consequences on this species’ foraging success and fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Such information can now be gathered using AT to inform spatial management plans, identify essential habitats, perform environmental risk assessments, or assess the impacts on marine biodiversity before and after the construction of infrastructures. For example, AT has been successfully employed to detect the behavioral impacts of shipping (Ivanova et al, 2020;Sertlek et al, 2019), dredging (Castro-Santos et al, 2019;Wenger et al, 2017) and seismic surveys (Slabbekoorn et al, 2019;van der Knaap et al, 2021van der Knaap et al, , 2022, identifying management and policy implications. Therefore, this tool should be widely promoted given the undergoing or planned expansion of blue economy marine infrastructures, namely renewable energy infrastructures and deep-sea mining, respectively, both of which may have confirmed or suspected severe impacts (Masmitja et al, 2020).…”
Section: S Dg14 Targ E T 2-acous Ti C Tr Ack Ing a S A Tool For O Ce ...mentioning
confidence: 99%
“…Measuring the effects of these disturbances on aquatic animal behavior has been impaired by the lack of appropriate tools (Barcelo-Serra et al, 2021). However, recent AT studies managed to reveal significant impacts of seismic surveys (Figure 2), shipping, and wind farm noise on fish behavioral patterns (Davidsen et al, 2019;Ivanova et al, 2020;Rider et al, 2021;Wardle et al, 2001;Winter et al, 2010) and potential effects on population survival and fisheries productivity (Bruce et al, 2018;Hubert et al, 2020;van der Knaap et al, 2021van der Knaap et al, , 2022. The benefits of AT to measure the effects of light pollution is extended to other no-fish taxa.…”
Section: S Dg14 Targ E T 1-acous Ti C Tr Ack Ing To Me a Sure The Eff...mentioning
confidence: 99%
See 1 more Smart Citation